The Role of E-Participation in Building Public Trust and Readiness for E-Voting: A Systematic Review - Muhammad Naufal Sulaiman; Apol Pribadi Subriadi; Feby Artwodini Muqtadiroh (Journal of Information System and Informatics, 2026)
Digital Electronic voting (e-voting) success relies heavily on institutional trust and public readiness, yet existing literature predominantly emphasizes technical specifications over socio-political factors. This study addresses this gap by systematically synthesizing how e-participation mechanisms contribute to public trust and readiness for e-voting adoption. A systematic Literature review (SLR) following the PRISMA 2020 framework was conducted, analyzing 40 peer-reviewed journal articles published between 2020 and 2025 from reputable databases. The finding reveal that readiness is influenced by interrelated factors, primarily trust in e-voting systems (n=9), technology (n=7), and government (n=6), alongside digital literacy (n=6) and ICT access (n=5). Crucially, the analysis identifies that e-participation mechanisms specifically online consultations and feedback loops serve as foundational learning tools that foster the necessary social readiness and mitigate resistance toward new electoral technologies. The Study contributes a conceptual reframing of e-participation as a prerequisite mechanism for building digital trust, rather than just a democratic feature. These findings provide guidance for policymakers designing inclusive and trustworthy digital electoral systems.